2020
DOI: 10.1111/jvim.15818
|View full text |Cite
|
Sign up to set email alerts
|

Palliative ventriculoperitoneal shunting in dogs with obstructive hydrocephalus caused by tumors affecting the third ventricle

Abstract: Background Hypertensive or obstructive hydrocephalus is a common complication in dogs with tumors affecting the third ventricle for which few therapeutic options are available. Objectives To describe signalment, neurological status, and pre‐ and postsurgical findings, complications and survival time in 4 dogs with obstructive hydrocephalus caused by third ventricle tumors that were palliatively treated using ventriculoperitoneal shunting (VPS). Animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Choroid plexus tumors are rare tumors in cats, and the reported clinical signs are variable including seizures, blindness and altered mental status ( 1 , 9 ). Although not mentioned if the cats in these studies had increased ICP, in people and dogs choroid plexus tumors are widely associated with raised ICP ( 2 , 10 ). Ventricular shunt placement has been shown to significantly improve clinical symptoms of human patients with increased ICP secondary to brain tumors ( 11 ).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Choroid plexus tumors are rare tumors in cats, and the reported clinical signs are variable including seizures, blindness and altered mental status ( 1 , 9 ). Although not mentioned if the cats in these studies had increased ICP, in people and dogs choroid plexus tumors are widely associated with raised ICP ( 2 , 10 ). Ventricular shunt placement has been shown to significantly improve clinical symptoms of human patients with increased ICP secondary to brain tumors ( 11 ).…”
Section: Discussionmentioning
confidence: 93%
“…A comparison between dogs with congenital hydrocephalus treated with VPS or medical management showed similar outcomes, although the median follow up time was only 9 months for medical and 15 months for surgical management ( 31 ). However, a case series with dogs with hydrocephalus secondary to tumors of the third ventricle found that the ICP measured considerably higher (28 mmHg and 31 mmHg) than the intracranial pressures found in dogs with communicating internal hydrocephalus (mean 8.8 mmHg, range from 3 to 18 mmHg) ( 2 , 32 ). In these dogs with hydrocephalus secondary to III ventricle tumors, their clinical signs were not improved by medical management but significantly improved after being treated with VPS placement ( 2 ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations